Nitrous Oxide Emissions and Carbon Sequestration in Turfgrass: Effects of Irrigation and Nitrogen Fertilization (Year 1) - R. Braun; D. Bremer; J. Fry (Kansas Agricultural Experiment Station Research Reports, 2016)
In this study, annual nitrous oxide (N2O) emissions were greatest in urea and least in untreated (no N) among treatments. Differences were negligible due to irrigation treatment. Irrigation levels may be decreased further in the final year to induce slight stress on the low irrigation treatment. All fertilizer treatments maintained acceptable quality, however the controlled-release fertilizer resulted in more consistent visual quality ratings compared to urea and untreated. Urea fertilizer had higher peak fluxes after fertilization and overall annual emissions than polymer-coated N-fertilizer. Thus, controlled released N fertilizers, such as polymer-coated urea, in turfgrass systems could potentially help mitigate N2O emissions.
Keywords: nitrous oxide; greenhouse gas; climate change; turfgrass